Exploring rural enterprises new perspectives on research, policy & practice - Henry, Colette; McElwee, Gerard (Emerald, 2014)
This fourth volume in the Contemporary issues in entrepreneurship research series - edited by Colette Henry and Gerard McElwee - draws together contemporary research contributions that critically explore a range of issues relating to rural enterprise. The chapters in this volume consider the various iterations of rural enterprise noting the underpinning synergy of the rural context but exploring the diversity of how this is articulated. Within this overarching theme, the volume contributors explore topics ranging across issues relating to networks, social exclusion, communities and gender. Research is presented from a range of different countries, including the UK, Ireland, Bulgaria, New Zealand, and Africa. The various studies use conceptual frameworks that underpin generic entrepreneurial theory and practice but recognise that their articulation within the rural environment acts as a particular lens to offer a novel perspective upon these issues. In offering their insightful critique, Henry & McElwee draw attention to the critical nature of rurality and its impact on entrepreneurship, thus furthering understanding in this area.
Keywords: Rural industries -- Research.; Entrepreneurship -- Research.; Enterprise zones, Rural -- Research.; elektronické knihy; electronic books